2014
DOI: 10.2112/jcoastres-d-13-00016.1
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Eco-Hydrological Environment in the Yellow River Delta Wetland

Abstract: We investigated the relationship between groundwater head and oceanic tidal fluctuations in the Yellow River Delta wetland through on-site hydrological monitoring. Shallow groundwater heads were obviously affected by oceanic tide along the coastal zone. The ranges of the wetland zone can be readily assessed by measuring fluctuation amplitudes or lags. The results show that the influence radius is approximately 12 km to 18 km (when the correlation coefficient is 0.7 to 0.8) under the joint actions of oceanic ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Thus, large quantities of water are expected to be stored in the underlying aquifer (Moore 1999), and these paleo-channels may serve as potential pathways for discharging groundwater (Stieglitz 2005). Gao et al (2014) found that shallow groundwater heads are obviously affected by tides as far as 18 km inland from the Yellow River estuary, which also demonstrates the interactions between the subterranean estuary and the sea. The implementation of WSRS leads to a huge discharge of water, dissolved solids and sediment with a remarkable pulsed impact on the estuary.…”
Section: Influence Of the Wsrs On Sgdmentioning
confidence: 94%
“…Thus, large quantities of water are expected to be stored in the underlying aquifer (Moore 1999), and these paleo-channels may serve as potential pathways for discharging groundwater (Stieglitz 2005). Gao et al (2014) found that shallow groundwater heads are obviously affected by tides as far as 18 km inland from the Yellow River estuary, which also demonstrates the interactions between the subterranean estuary and the sea. The implementation of WSRS leads to a huge discharge of water, dissolved solids and sediment with a remarkable pulsed impact on the estuary.…”
Section: Influence Of the Wsrs On Sgdmentioning
confidence: 94%
“…The hydrodynamics near Yellow River mouth is dominated by semidiurnal tides (tidal range around 1.5-2.0 m) and wind driven waves and residual currents (Bi et al, 2014). For the groundwater system of YRD, Gao et al (2014) divided coastal wetlands into groundwater seepage zone, tidal-induced transitional zone, and tidal zone, where the influence radius of oceanic tide is approximately 12-18 km. Integrated study on the interaction between freshwater inflow, sea water, and groundwater is urgently needed for the understanding of the hydrological processes of the YRD wetland.…”
Section: A Changing Ecohydrological Environment Of Yrd Wetlandmentioning
confidence: 99%
“…Like many of the large deltas around the world (Blum and Roberts, 2009;Syvitski et al, 2009), the YRD is facing increasing risks of degradation due to anthropogenic and natural forces (Bi et al, 2014;Cui et al, 2009;Gao et al, 2014;Kong et al, 2015;Wang et al, 2007). The fundamental changes in land-building and land loss in the YRD plain are rooted in the supply of water and sediment from Yellow River that undergone major shifts in the river's course since the delta's formation in 1855.…”
Section: Introductionmentioning
confidence: 99%
“…Combining with the actual situation of the local nature, social environment and economy, CRI system is chosen for water treatment in Phoenix River (Du, Xu, and Wang, 2009;Gao, Liu, and Zhao, 2014;Ma, Lu, and Wang, 2012;Xia, Wu, and Cao, 2009). Advantages of CRI system are: (1) Effect of wastewater treatment is better than that of the traditional activated sludge process.…”
Section: Land Treatment Systemmentioning
confidence: 99%